Modified thoraco-mediastinal plication (Andrews thoracoplasty) for post-pneumonectomy empyema: experience with 30 consecutive cases(†) - Botianu, Alexandru-Mihail (Oxford University Press, 2013)
OBJECTIVES: The aim of our study is to evaluate the results of thoraco-mediastinal plication for the treatment of post-pneumonectomy empyema. METHODS: From 1 January 1985 to 1 January 2011, 30 patients underwent post-pneumonectomy empyema through a modified thoraco-mediastinal plication procedure (Andrews thoracoplasty). Indications for pneumonectomy included cancer (25 cases), tuberculosis (3 cases), and bronchiectasis (two cases). Rib resection was performed according to the topography of the cavity, ranging between 5 and 10. Neighbourhood muscle flaps were used in 22 cases but extensive mobilization was performed only in our last 4 cases, the aim of the procedure being the complete obliteration of the infected space. Bronchial fistula was present in 14 cases and was closed and reinforced with the use of flaps (intercostal 12 cases, serratus 1 case, and omentum 1 case). RESULTS: Overall mortality was 6.7% (2 cases); 2 patients (6.7%) presented with recurrence of the empyema requiring an open-window procedure and another patient (3.3%) presented with local tumoral recurrence. Intensive care unit hospitalization ranged between 1 and 14 days, with a median of 4 days, while overall postoperative hospitalization ranged between 23 and 52 days with a median of 32 days, the patients being discharged with healed wounds. Kaplan–Meier analysis of the oncologic patients showed a median survival of 41 months from thoraco-mediastinal plication. The presence of bronchial fistula had no statistically significant impact on the immediate outcome (mortality, need for postoperative prolonged mechanical ventilation, intensive care and overall postoperative hospitalization, P > 0.05 for all the parameters). CONCLUSIONS: Space-filling procedures are a valuable option for treating post-pneumonectomy empyema. The major advantages are the complete obliteration of the infected space and the quick healing from a single procedure; the major disadvantages are the magnitude of the procedure (with associated mortality and morbidity) and the permanent chest mutilation. Several technical details may improve the results and reduce the chest wall mutilation.